Effects of Focus Geometry on the Hard Rock-Cutting Performance of an Abrasive Waterjet. (30th January 2020) - Cha, Yohan; Oh, Tae-Min; Cho, Gye-Chun
Abstract : Abrasive waterjets are being increasingly used in civil engineering for rock and concrete cutting, particularly for the demolition or repair of old structures. The energy of an abrasive waterjet is primarily provided by the accelerated abrasive. The momentum transfer during mixing and acceleration determines the abrasive velocity, which affects the cutting performance. Meanwhile, the geometry of the focus at which mixing occurs influences the momentum transfer efficiency. In this study, the effects of the focus geometry on the optimum abrasive flow rate (AFR) and momentum transfer characteristics in hard rock cutting were investigated. Experiments were conducted using granite specimens to test the AFR under different focus geometry conditions such as diameter and length. The results show that the focus geometry significantly affects the maximum cutting depth and optimum AFR. The maximum cutting energy was analyzed based on the cutting efficiency of a single abrasive particle. In addition, the momentum transfer parameter (MTP) was evaluated from the empirical relationship between the maximum energy and the cutting depth for granitic rocks. Accordingly, a model for estimating the MTP based on the AFR was developed. It is expected that the results of this study can be employed for the optimization of waterjet rock cutting.